Introduction of Renal Key Performance Indicators Associated with Increased Uptake of Peritoneal Dialysis in a Publicly Funded Health Service. Issue 2 (March 2017) - Toussaint, Nigel D.; McMahon, Lawrence P.; Dowling, Gregory; Holt, Stephen G.; Smith, Gillian; Safe, Maria; Knight, Richard; Fair, Kathleen; Linehan, Leanne; Walker, Rowan G.; Power, David A.
Background: Increased demand for treatment of end-stage kidney disease has largely been accommodated by a costly increase in satellite hemodialysis (SHD) in most jurisdictions. In the Australian State of Victoria, a marked regional variation in the uptake of home-based dialysis suggests that use of home therapies could be increased as an alternative to SHD. An earlier strategy based solely on increased remuneration had failed to increase uptake of home therapies. Therefore, the public dialysis funder adopted the incidence and prevalence of home-based dialysis therapies as a key performance indicator (KPI) for its health services to encourage greater uptake of home therapies. Methods: A KPI data collection and bench-marking program was established in 2012 by the Victorian Department of Health and Human Services, with data provided monthly by all renal units in Victoria using a purpose-designed website portal. A KPI Working Group was responsible for analyzing data each quarter and ensuring indicators remained accurate and relevant and each KPI had clear definitions and targets. We present a prospective, observational study of all dialysis patients in Victoria over a 4-year period following the introduction of the renal KPI program, with descriptive analyses to evaluate the proportion of patients using home therapies as well as home dialysis modality survival. Results: Following the introduction of the KPI program, the net growth of dialysis patient numbers in Victoria remained stable over 4 years, at 75 – 80 per year (approximately 4%). However, unlike the previous decade, about 40% of this growth was through an increase in home dialysis, which was almost exclusively peritoneal dialysis (PD). The increase was identified particularly in the young (20 – 49) and the elderly (> 80). Disappointingly, however, 67% of these incident patients ceased PD within 2 years of commencement, 46% of whom transferred to SHD. Conclusions: Introduction of a KPI program was associated with an increased uptake of PD but not home HD. This change in clinical practice restricted growth of SHD and reduced pressure on satellite services. The effect was offset by a modest PD technique survival. Many patients in whom PD was unsuccessful were subsequently transferred to SHD rather than home HD.